Prison Islamic Boarding School: Efforts to Instill Morals in Prisoners in Correctional Institutions - Mohammad 'Ulyan; Fauzi; Nur Rofiq (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
Correctional institutions have complicated problems; the number of inmates is already over-capacity, prisons are places for courses on crime and terrorism, budget requirements are swelling, and the number of prison riots is increasing. Health problems exacerbate this during the covid 19 pandemic. The research method in this article uses qualitative research methods with a library approach. This paper contributes to the improvement of the system, especially in fostering Islam in correctional institutions through the pesantren program. The results state that it is necessary to strengthen the role of pesantren in correctional institutions to shape prisoners' morals for the better.